Randomized (CO)mparison of (TRI)fecta and (P)erimount Magna Ease Supraannular Aortic Xenografts—CO.TRI.P Study - Van Linden, Arnaud; Arsalan, Mani; Körschgen, Thore; Blumenstein, Johannes; Kempfert, Jörg; Hecker, Florian; Walther, Thomas (The Thoracic and Cardiovascular Surgeon, 2019)
Background Modern supraannular aortic xenografts offer a special design, thus providing maximized opening area for improved hemodynamics. The aim of this study was a prospectively randomized comparison of the Trifecta and the Perimount Magna Ease valves based on metric annulus sizing.Methods A total of 100 patients with aortic stenosis undergoing aortic valve replacement (AVR) with or without concomitant procedures were prospectively included. After decalcification of the annulus, stratified intraoperative randomization was performed. The diameter of the aortic annulus was measured using metric Hegar dilators and randomization was based on this metric annulus diameter. Exercise echocardiography was performed at 10-month follow-up.Results Mean age was 69 years, with 36% female. Predominant implanted valve sizes were 23 mm (39%) and 25 mm (32%). Unadjusted mean pressure gradient was significantly lower and effective orifice area larger for the Trifecta group (10.8 ± 5 vs. 13.2 ± 4 mm Hg, p = 0.02 and 1.93 ± 0.39 vs. 1.70 ± 0.30 cm2, p = 0.002) at discharge. In patients with small annuli, based on the metric annulus size there were no significant differences in gradients or the orifice area. At exercise echocardiography follow-up, there were no significant hemodynamic differences between both prostheses.Conclusions The Trifecta and the Perimount Magna Ease prostheses both show excellent hemodynamic performance after AVR. In patients with larger annuli, the Trifecta valve seems to be even superior to the Magna Ease, which may be advantageous in obese patients.
Keywords: aortic valve and root; echocardiography; all modalities; applications; heart valve surgery; xenograft